PENGEMBANGAN PERANGKAT PEMBELAJARAN MODEL BELAJAR DI LINGKUNGAN (OUTDOOR LEARNING)UNTUK MATA KULIAH MORFOLOGI TUMBUHAN - Suryani, Erni; Jekti, Dwi Soelistya Dyah; Ramdani, Agus (Postgraduate, University of Mataram, 2015)
To improve students' academic ability is necessary to the development of innovation in learning. Development of the learning device will be able to improve the quality of content, process, and learning outcomes of students. In order to achieve these objectives, the steps that need to be done is to analyze the competencies or learning objectives, identifying the characteristics of learners and establish a learning environment. To develop the necessary creativity learning educators to create interesting learning activities. Development of a learning device demands of the curriculum in higher education system. According Kepmendiknas 232 / U / 2000 higher education curriculum is a set of plans and arrangements regarding content and study materials and lessons as well as the delivery and assessment are used as guidelines for the organization of teaching and learning in higher education. This research aims to develop outdoor learning model learning device that is expected to improve the learning outcomes of students. Development of the learning device refers to a model of Dick and Carey. Developed learning tools such as syllabi, lecture events unit, student activity sheet and instruments of learning outcomes in the course of plant morphology. Data were collected using instruments feasibility of device which is validated by validator. The results showed that the learning device such as syllabi, lecture events unit, student activity sheet gets categorized, achievement test gets categorized as very feasible to be implemented on plant morphology courses for students of the second semester.Keywords: Devices, outdoor learning, learning outcomes